Mental health status and challenges faced by grade five schoolarship holders attending grade six classes of national schools in the Galle Municipal Council Area - Senaratne, P.A.S (My University, 2010)
Out of total 708 Grade five scholarship holders in Grade six classess, in seven National schools in Galle MCA, 640 students participated in the study. The non response rate was 9.6 percent. THe self reported version of Sinhala validated strengh and difficuties questionnaire (SDQ) was used to assess the mental health status, while a self administered questionnaire was used to obtain the basic socio-demographic profile and the challenges faced by scholarship holders. Data was analyzed using SPSS 16.0 for Windows. Students were categorized in to scales of mental health symptoms according to the British cut off values. Among 640n scholarship holders who participated in the present study 10.3 percent of children were identified as having abnormal range of scores. This was a low value when compared to values obtained in studies in Sri Lankan context among adolescents. Peer problems were more prevalent ( 18.9 percent) among scholarship holders while conduct and hyperactivity problems scored 9.7 percent and 8.6 percent respectively. Scholarship holders had lowest scores ( 5.2 percent) for emotional and pro-social problems. Scholarship holders are a special group of children with relatively low prevalence of mental health problems when compared to prevalence of mental health problems reported in othe community and school based stuides in Sri Lanka. However there is a reasonable proporation of children who need some psychological support to overcome the challenges which they have faced. The findings of present study emphasized the need for developing programmes aimed at children to cope with stressful situations train and sensitize the teachers and parents regarding child and adolescent mental health problems and strengthen the school mental health programme.